Overall Cultural Competence in the Context of Realization of the Competence Approach - Shpytalevs’ka, Galina (Pedagogical Discourse, 2011)
The article analyzes the concept of „overall cultural competence”, addresses issues that relate to the formation of the younger generation in the context of the competence-based approach. It is shown how the focus is in the government documents regarding to the need and importance of the formation of common cultural competency training as a necessary condition for a highly cultured, competent person.